Communication Strategies and Plans on the Impact of Climate Change on Cocoa Production in Ghana: A Case of COCOBOD - Amoako, Maybel (UniMAC - GIJ, 2020)
This long essay assesses communication strategies and plans on the impact of climate change on cocoa production in Ghana. The study adopted the mixed research methodology comprising both qualitative and quantitative to establish the impact of climate change on cocoa production using communication strategies and plans as the main variables. Primary data were used in the form of interviews of certain key directors and public affairs officials of COCOBOD. The Cocoa Research Institute of Ghana in anticipation of future climate change and taken cognizance of the debilitating effect of drought on cocoa production has continuously adopted a communication strategy by giving farmers education on climate-related issues with the use of a unit called the Social Science and Statistics Unit (SSSU) with use of flip charts which has a representation of the scientific ideas concerning climate change in pictorial form for the farmers to better understand. Information gathered from the interview revealed that COCOBOD communicating plan is inbuilt in the various program being implemented to enhance cocoa productivity. And this include the use of both print and electronic media, and increasing the number of extension agents to increase the contact hours between farmers and extension agents. In determining the best communication plan to address climate change on cocoa production in Ghana, COCOBOD engages cocoa farmers and affected communities are engaged regularly through town halls meetings, durbars, and phone-in program to collect inputs and plans from the design stage to the implementation phase.
THESIS